2021
DOI: 10.1186/s12870-021-03047-w
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the mechanism of the effects of rhizosphere microorganisms on the quality of authentic Angelica sinensis under different soil microenvironments

Abstract: Background Angelica sinensis (Oliv.) Diels (A. sinensis) is a Chinese herb grown in different geographical locations. It contains numerous active components with therapeutic value. Rhizosphere microbiomes affect various aspects of plant performance, such as nutrient acquisition, growth and development and plant diseases resistance. So far, few studies have investigated how the microbiome effects level of active components of A. sinensis. This study investigated whether changes in rhizosphere mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Actinobacteria, Acidobacteria, and Proteobacteria were the top three abundant bacterial phyla across the three treatment groups. These top three bacterial phyla were also found abundantly in the previous studies conducted in Yunnan province ( Tan et al, 2017 ; Yang et al, 2020 , 2021 ; Kui et al, 2021 ; Zhu et al, 2021 ); however, Proteobacteria was the most dominant bacterial phyla in these studies. The relative abundance of Actinobacteria was first increased from CK to Y5 and then decreased from Y5 to Y20.…”
Section: Discussionsupporting
confidence: 51%
“…Actinobacteria, Acidobacteria, and Proteobacteria were the top three abundant bacterial phyla across the three treatment groups. These top three bacterial phyla were also found abundantly in the previous studies conducted in Yunnan province ( Tan et al, 2017 ; Yang et al, 2020 , 2021 ; Kui et al, 2021 ; Zhu et al, 2021 ); however, Proteobacteria was the most dominant bacterial phyla in these studies. The relative abundance of Actinobacteria was first increased from CK to Y5 and then decreased from Y5 to Y20.…”
Section: Discussionsupporting
confidence: 51%
“…Co-occurrence network of the medicinal components and differential microbial taxa in rhizosphere of A. sinensis. Chen et al 10.3389/fpls.2022.1005711 Extensive studies have proved the soil microenvironment influenced the growth and level/type of active components in A. sinensis (Zhu et al, 2021). In this study, we found that the developmental stage is also an important factor affecting the accumulation of medicinal components of A. sinensis.…”
Section: Figurementioning
confidence: 49%
“…These observations indicated that continuous cropping destroyed the balance of original microbial flora and resulted in the imbalance of rhizosphere microecology (Dong et al, 2016 ; Li et al, 2021 ), which would have an important impact on the quality of medicinal plants. Zhu et al ( 2021 ) found that different soil microenvironments significantly affected the growth and active components of Angelica sinensis , and the key bacterial species may be the key factor determining the quality of A. sinensis , which indicated that the soil microenvironment contributed to the growth and accumulation of active components of medicinal plants.…”
Section: Introductionmentioning
confidence: 99%